Solar Energy Harvester for Industrial Wireless Sensor Nodes - Ibrahim, R. (Elsevier B.V., 2017)
Advancement in recent wireless technology has triggered the need for devices to run on independent power sources. This is evident especially with the wireless sensor network (WSN). This can be accomplished via harvesting energy from the surrounding environment such as solar, wind etc. These enery harvesting devices can power the wireless sensor nodes either directly of in conjunction with a battery. This paper presents the development of a solar energy harvesting mechanism for WirelessHART sensor node using photovoltaic (PV) cell array. Experimental results on the WirelessHART nodes proved that the developed harvester is capable of powering the nodes. © 2017 The Authors.